A biotecnologia vegetal como alternativa para a cotonicultura familiar sustentável - Silva, Kléptura de Oliveira e (2006)
This paper aims to describe the familiar cotton culture in the districts of Tangará and Triunfo Potiguar, located in the state of Rio Grande do Norte. It relates specific problems that small cotton agriculturists face in the cotton production and sale as well as their perception in relation to public policies that have been put into practice in these districts. The research revealed soils with potentiality for the cotton culture, but that are not being cultivated for anything else but subsistence, not being able to become productive, specifically through the cotton culture. That activity should be practiced so that it preserves the environment and the familiar farmers themselves, since it was verified they are constant1y exposed to health problems due to insecticides use. In what refers to fomentation policies it was observed that bureaucracy delays the liberation of the money destined to production, seeds delivery and other actions related to production and commercialization. Some procedures such as information and training about productivity development and attention with the environrnent and infrastructure are recommended. The results indicate lack of investments, rural credit and technical help, main1y in Triunfo Potiguar. There is unanimity, from the rural farmers of that district in what refers to the desire of improving the production and remaining in that activity. In this sense, the contribution of this research for the most appropriate culture production can be materialized through the technique of tissue's culture, aimed at obtaining plants that are resistant to diseases. The data indicated that the hormonal supplementations used induced regenerative calluses making in vitro morphogenesis possible in alI tested varieties. The use of the activated coal antioxidant was efficient, reducing oxidation, however not suppressing it. The results lead to an opportunity for the familiar tàrmers from Rio Grande do Norte enlarge the cotton culture, because to obtain plants that are resistant to diseases implies in insecticides reduction, propitiating smaller impact to the atmosphere and less cost